2021
DOI: 10.1021/acsbiomaterials.1c00804
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Corona Composition and Cell Uptake to Identify Proteins Affecting Nanoparticle Entry into Endothelial Cells

Abstract: The formation of the biomolecule corona on the surface of nanoparticles upon exposure to biological fluids critically influences nanocarrier performance in drug delivery. It has been shown that in some cases corona proteins can mediate specific nanoparticle interactions with cell receptors. Within this context, in order to identify corona proteins affecting nanoparticle uptake, in this work, correlation analysis is performed between the corona composition of a panel of silica nanoparticles of different sizes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 57 publications
5
33
0
Order By: Relevance
“…It is worth mentioning that both agglomeration size (Supporting Information, Excel S1) and protein corona (data are not displayed) of nano-TiO 2 are affected by the composition of medium (especially the type and concentration of proteins) and, consequently, influence the uptake of nanoparticles by cells. Moreover, the dispersion process of the nano-TiO 2 used also affects its cytotoxicity . Although these factors cannot be further analyzed in this study because they have not been reported in all the included studies, their roles in the effects of nano-TiO 2 on cell cycle cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that both agglomeration size (Supporting Information, Excel S1) and protein corona (data are not displayed) of nano-TiO 2 are affected by the composition of medium (especially the type and concentration of proteins) and, consequently, influence the uptake of nanoparticles by cells. Moreover, the dispersion process of the nano-TiO 2 used also affects its cytotoxicity . Although these factors cannot be further analyzed in this study because they have not been reported in all the included studies, their roles in the effects of nano-TiO 2 on cell cycle cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Based on similar observations, more studies are focusing on the screening of the corona forming on panel of nanoparticles as a novel tool to identify molecules that can promote or reduce uptake by cells [155][156][157][158]. We performed similar studies using silica nanoparticles of different size and surface functionalization, as well as liposomes of different charge which showed very different uptake levels by cells [153,159]. Similarly, we have used a panel of different nanoparticles thus different corona to identify receptors involved in nanoparticle uptake into endothelial cells from different organs (Aliyandi et al unpublished) [160].…”
Section: Interactions With Biological Fluidsmentioning
confidence: 93%
“…Interestingly, the authors identified this protein as a major component in the corona forming on PEGylated nanoparticles and suggested that it is this specific protein in the corona to confer the socalled PEG "stealth-effect", as opposed to the overall reduced protein binding. Recently reduced uptake has been observed also for nanoparticles with a corona rich in histidine rich glycoprotein [153,154]. Interestingly, reduced uptake could be achieved also when pre-coating nanoparticles with an artificial corona of histidine rich glycoprotein [153].…”
Section: Interactions With Biological Fluidsmentioning
confidence: 97%
See 2 more Smart Citations